2022
DOI: 10.1002/adhm.202101948
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Primary Salivary Gland Acinar Cell Clusters and Intercalated Ducts (AIDUCs) within Matrix Metalloproteinase (MMP)‐Degradable Hydrogels to Maintain Tissue Structure and Function

Abstract: Progress in the development of salivary gland regenerative strategies is limited by poor maintenance of the secretory function of salivary gland cells (SGCs) in vitro. To reduce the precipitous loss of secretory function, a modified approach to isolate intact acinar cell clusters and intercalated ducts (AIDUCs), rather than commonly used single cell suspension, is investigated. This isolation approach yields AIDUCs that maintain many of the cell-cell and cell-matrix interactions of intact glands. Encapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 99 publications
(167 reference statements)
0
13
0
Order By: Relevance
“…Cells were centrifuged, then resuspended in HBSS with 15 mM HEPES and passed through 100 μm and 20 μm mesh filters to isolate clusters between 20-100 μm. The digestion protocol produces cell cluster sizes evenly distributed between 20 to 100 μm [33]. The isolated clusters were combined with hydrogel precursor solution and seeded in MB array-based chips as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were centrifuged, then resuspended in HBSS with 15 mM HEPES and passed through 100 μm and 20 μm mesh filters to isolate clusters between 20-100 μm. The digestion protocol produces cell cluster sizes evenly distributed between 20 to 100 μm [33]. The isolated clusters were combined with hydrogel precursor solution and seeded in MB array-based chips as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Dispersed SMG clusters were subsequently passed through 100 and 20 μm filters to isolate clusters between 20–100 µm. The digestion protocol produces cell cluster sizes evenly distributed between 20 to 100 µm [ 32 ]. The isolated clusters were re-suspended in base culture medium, defined below.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Song et encapsulation of primary SG acinar cell clusters and intercalated ducts (AIDUCs) in 3D hydrogels to form SG microtissues. 58 The authors reported that the cell clusters maintained key SG-specific markers like NKCC1, PIP, and AQP5 in 3D for 14 days in culture and responded to stimulation by purinergic agonists. 1.2.…”
Section: Understanding the Sg Cell Niche�sourcing And Isolation Strat...mentioning
confidence: 99%